Ensuring Quality Medicine is not a Single Event but Rather Combines Effects of a Pharmaceutical Company - Ahmed, Rashed (RADINKA JOURNAL OF HEALTH SCIENCE, 2024)
The article "Ensuring Quality Medicine is Not a Single Event but a Combined Effort of a Pharmaceutical Company" explores the multifaceted approach required to maintain high standards in pharmaceutical manufacturing. It emphasizes that quality assurance in medicine production is not an isolated event but a continuous, integrated process involving multiple departments and stages. The article highlights the roles of research and development, rigorous clinical trials, regulatory compliance, and robust manufacturing practices in ensuring the efficacy and safety of medicines. It also discusses the importance of quality control measures, such as stringent testing protocols and regular audits, to detect and mitigate potential issues early. The collaboration between different teams within a pharmaceutical company, including scientists, engineers, and quality assurance professionals, is crucial for sustaining quality throughout the product lifecycle. Moreover, the article addresses the necessity of adhering to global standards and guidelines, such as Good Manufacturing Practices (GMP), to ensure consistency and reliability in drug production. By fostering a culture of continuous improvement and vigilance, pharmaceutical companies can effectively safeguard public health and maintain trust in their products. This holistic approach underscores that delivering quality medicine is an ongoing commitment requiring coordinated efforts across the entire organization.